In Quest of the Meaning of Images – Viewers as Actors (KULT_online, 2010)
In the fifteenth century prints had a wide range of functions and meanings. The specific meaning of reproducible images changed according to the interplay between the viewer and the printed image. David S. Areford's study shows how viewers personalise their standardised prints and conform them to their own needs. The book is a methodically visual-culture study that could also be read as a case for the materiality of the printed image.